2011
DOI: 10.1186/1471-2148-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Does body posture influence hand preference in an ancestral primate model?

Abstract: BackgroundThe origin of human handedness and its evolution in primates is presently under debate. Current hypotheses suggest that body posture (postural origin hypothesis and bipedalism hypothesis) have an important impact on the evolution of handedness in primates. To gain insight into the origin of manual lateralization in primates, we studied gray mouse lemurs, suggested to represent the most ancestral primate condition. First, we investigated hand preference in a simple food grasping task to explore the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 50 publications
8
50
1
Order By: Relevance
“…In addition, M. murinus essentially exhibited a whole-hand grip between the palm and all the fingers and preferred one hand in its first contact with the food. Therefore, the mouth was not always involved in the process of static food grasping, in contrast to what has been reported previously [Bishop, 1964;Dodson et al, 1992;Ward and Hopkins, 1993;Scheumann et al, 2011]. The nature of the food and the omnivorous diet of M. murinus may be linked to the degree of hand use.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In addition, M. murinus essentially exhibited a whole-hand grip between the palm and all the fingers and preferred one hand in its first contact with the food. Therefore, the mouth was not always involved in the process of static food grasping, in contrast to what has been reported previously [Bishop, 1964;Dodson et al, 1992;Ward and Hopkins, 1993;Scheumann et al, 2011]. The nature of the food and the omnivorous diet of M. murinus may be linked to the degree of hand use.…”
Section: Discussioncontrasting
confidence: 51%
“…In comparison, Prosimii (lemuriforms and lorisiforms) are thought to be less variable in grip posture, to show no digital individualization and to use the mouth for grasping more often [Bishop, 1964]. In order to grasp static foods, the lemuriforms appear to prefer to grasp with the mouth as shown both by observations in the wild [Petter, 1962] and studies on manual preference [Larson et al, 1989;Ward et al, 1990;Milliken et al, 1991a;Dodson et al, 1992;Ward and Hopkins, 1993;Ward, 1995;Leliveld et al, 2008;Nelson et al, 2009;Scheumann et al, 2011]. However, these studies on manual preference often adopted protocols forcing the subjects to take static food through a wire mesh or a slot with their hand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray mouse lemurs feed primarily on fruits and arthropods in the wild (Dammhahn and Kappeler 2008;Siemers et al 2007). Laboratory studies have shown that they preferentially use the mouth to grasp static food items such as fruits (Reghem et al 2011;Scheumann et al 2011;Toussaint et al 2013;Ward and Hopkins 1993). However, the use of the hands increases when grasping mobile prey such as insects (Toussaint et al 2013), a fact supported by observations in the wild (Charles-Dominique 1977;Martin 1972a, b;Siemers et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…One or both hands are typically used to catch fast moving foods, e.g., insects, particularly in platyrrhines, strepsirrhines, rats, opossums, and kinkajous (Charles-Dominique 1977;Ivanco et al 1996;Martin 1972a, b;McClearn 1992;Nekaris 2005;Niemitz 1984;Peter 1962). Yet, many of these species preferentially use the mouth to grasp static foods such as fruit (Pollock 1977;Reghem et al 2011;Rothe 1971;Scheumann et al 2011;Singer and Schwibbe 1998;Toussaint et al 2013;Whishaw et al 1998). However, the substrates used during food grasping are rarely considered and as such it remains largely unknown how these two parameters interact.…”
Section: Introductionmentioning
confidence: 99%